Influência estrutural e tectônica no relevo do setor central do Planalto das Araucárias - Lima, Jacson Gosman Gomes de (2020)
The spatial section of this research covers an area of approximately 11,000 km2, located in the central sector of the Planalto das Araucárias. This geomorphological unit is supported by volcanic rocks of the Serra Geral Group, in the Paraná Basin. The main objective of this research was to verify the degree of structural and tectonic influence in the elaboration of the regional relief, from the study of structural lineaments that affected volcanic rocks. The methodology used integrated different research methods and techniques, among them: processing and interpretation of aeromagnetometric data; morphometric analysis of the drainage network and the relief (mapping of anomalies and drainage patterns; index “slope extension ratio - total and per RDE”, analysis of longitudinal river profiles, terrain roughness index - IRT, curvature of the terrain) ; construction of topographic profiles correlated with geomorphological surfaces, structural lineaments and lithological formations and mapping of brittle structures in the field. As a result of the research, three geotectonic compartments were established in the study area, these concordant with structural blocks in the Paraná Basin. It was also found that the subsurface structural lines (magnetic) show directional agreement with structural surface lines (faults / fractures; geomorphological lines and drainage lines), in many cases constituting structures that extend from the basement to the surface. The main structural trend in the study area is NW-SE. E-W being the youngest and linked to neotectonic movements. The morphotectonic influence is greater in the Chapecó River basin, where most of the tectonic indicators are concentrated (anomalous curves, drainage elbows, 1st order anomalies and structural lineaments). Despite this type of influence proving to be quite important in the study area, leading in many places to staggering the relief, creating systems of horsts, grabens and hemi-grabens, it is not the main responsible for the creation of geomorphological compartments. In contrast, the morphostructural influence linked to lithological differentiations, especially between acidic and basic volcanic rocks, is responsible for the existence of at least two morphostructural compartments in the study area. In this region where acid rocks predominate, usually summit surfaces, the relief is less dissected and with low slopes. Predominantly patterns of gently wavy shapes. In the domain of basic rocks, which corresponds to most of the study area, the relief is more dissected, more sloping, configuring as wavy to strongly wavy.